Ratchet Limit for Pressurized Pipes under Combined Biaxial Loadings. (2015) - Zheng, X.T.; Peng, H.Y.; Yu, J.Y.; Xu, J.M.; Wang, C.G.; Lin, W.
Abstract: Analytical ratchet limits of cylindrical pressure vessels and piping subjected to several typical cyclic non-proportional loading combinations, such as moment, torsion and thermal loading in practical engineering, were deduced theoretically according to the Non-Cyclic Method. The effects of radius ratio on ratchet limit of structures were investigated intensively. Results revealed that ratchet limit increases obviously with the increment of radius ratio. Moreover, several Bree-like diagrams under the corresponding loading conditions of this paper were obtained, which can be used to estimate ratchet limit of cylindrical pressure vessels and piping conveniently for engineering design.